2018
DOI: 10.1111/jfr3.12505
|View full text |Cite
|
Sign up to set email alerts
|

Multihazard simulation for coastal flood mapping: Bathtub versus numerical modelling in an open estuary, Eastern Canada

Abstract: Funding informationFonds Québécois de la recherche sur la nature et les technologies; Québec Ministry of Public Security Coastlines along the St. Lawrence Estuary and Gulf, Eastern Canada, are under increasing risk of flooding due to sea level rise and sea ice shrinking. Efficient and validated regional-scale coastal flood mapping approaches that include storm surges and waves are hence required to better prepare for the increased hazard. This paper compares and validates two different flood mapping methods: n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 100 publications
1
59
0
Order By: Relevance
“…Validation results for the mean water level (not included in Table 2) are virtually within a centimeter-scale deviation from the observations (r 2 = 0.99). indicators are under 0.07 cm, which is consistent with other studies (e.g., [33,71]). Overall, there is no tendency to over-or under-estimate wave heights in the nearshore zone (MBE close to 1 on both sensors) and regression lines have a nearly null intercept (a2 = ±0.01).…”
Section: Xbeach Validationsupporting
confidence: 93%
See 4 more Smart Citations
“…Validation results for the mean water level (not included in Table 2) are virtually within a centimeter-scale deviation from the observations (r 2 = 0.99). indicators are under 0.07 cm, which is consistent with other studies (e.g., [33,71]). Overall, there is no tendency to over-or under-estimate wave heights in the nearshore zone (MBE close to 1 on both sensors) and regression lines have a nearly null intercept (a2 = ±0.01).…”
Section: Xbeach Validationsupporting
confidence: 93%
“…Hourly wave boundary conditions for the 2010 flood simulation were extracted from WAVEWATCH III (see a description in Appendix A) with a 1 km grid resolution. The reader is referred to Didier et al [33] and Bernatchez et al [76] for a detailed explanation of the WW3 implementation in the EGSL. Based on the comparison between wave observations at the AWAC location and WW3 between 9-30 November 2015, Bernatchez et al [76] observed a negative bias of −0.253 m (RMSE = 0.297 m) attributed to (1) the insufficient resolution of the CFSR wind forcing model in coastal environments and (2) bathymetric effects, which are not resolved in the 1 km grid simulations.…”
Section: Offshore Waves and Water Levelsmentioning
confidence: 99%
See 3 more Smart Citations